2022
DOI: 10.1016/j.jinf.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody and T cell responses one year after COVID-19 and the booster effect of vaccination: A prospective cohort study

Abstract: Objectives : First, to describe SARS-CoV-2 T cell and antibody responses in a prospective cohort of healthcare workers that suffered from mild to moderate COVID-19 approximately one year ago. Second, to assess COVID-19 vaccine-induced immune responses in these prior-infected individuals. Methods : SARS-CoV-2-specific T cell and anti-SARS-CoV-2-Spike-RBD immunoglobulin G (IgG) responses in blood were determined before COVID-19 vaccination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 45 publications
5
39
0
Order By: Relevance
“…We found a relationship between anti-SARS-CoV-2 antibody formation and T cell responses, as documented by the fact that patients with antibody seroconversion (responders) had also higher levels of IFN-γ producing T cells at T2 ( Figure 4C ). These data confirm and expand previous findings by others ( 34 , 35 ). However, we also noticed patients with serological conversion that did not have detectable anti-SARS-CoV-2 IFN-γ T cell responses.…”
Section: Discussionsupporting
confidence: 93%
“…We found a relationship between anti-SARS-CoV-2 antibody formation and T cell responses, as documented by the fact that patients with antibody seroconversion (responders) had also higher levels of IFN-γ producing T cells at T2 ( Figure 4C ). These data confirm and expand previous findings by others ( 34 , 35 ). However, we also noticed patients with serological conversion that did not have detectable anti-SARS-CoV-2 IFN-γ T cell responses.…”
Section: Discussionsupporting
confidence: 93%
“…Ferrari et al and Manisty et al investigated differences in the post-vaccination response in people who had previously had COVID and suggested using different vaccination schedules in individuals with past infection [ 21 , 22 ]. Krammer et al and Mak et al additionally showed that in persons with past SARS-CoV-2 infection (even more than a year before vaccination), the administration of one vaccine dose produces the same humoral and cellular response as administration of two vaccine doses [ 4 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation of the symptom severity of SARS-CoV-2 infection with the antibody titre was also demonstrated by Wolszczak-Biedrzycka [ 14 ]. Although past infection is associated with preserving immunological memory even one year after infection [ 4 ], it can be expected to be weaker in certain groups. This includes the elderly, residents and staff of care homes, persons after paucisymptomatic infection and those with higher exposure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations